0900 The Impact of a Wii-based Home Exercise Program on Functional Capacity in Patients with COPD-OSA Overlap Syndrome. (27th April 2018) - Macrea, M; Oursler, K; Martin, T; ZuWallack, R
Abstract: Introduction: Patients who have both chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea (OSA) (OS, overlap syndrome), have increased cardiovascular morbidity and mortality, possibly due, in part, to nocturnal hypoxia with subsequent inflammation and endothelial dysfunction. Home-based exercise interventions that translate to a lifestyle with increased physical activity should improve functional status and may even reduce risk of cardiovascular-related events and death. We hypothesize that a home-based exercise program improves functional capacity in OS. Methods: OS patients enrolled in the Pulmonary Telehealth Clinic at the Salem Veterans Administration Medical Center were offered a 12-week home exercise program using a proprietary exercise program (Wii Fit). Exclusion criterion was the presence of a comorbid condition that would place the patient at undue risk for exercise. Patients were instructed to use the Wii Fit for 20 minutes at least twice a week for 12 weeks, using specific Wii Fit exercises. The intensity of these exercises ranged from 2.5 to 4 metabolic equivalents (METs). Weight, daily home exercise time and calories were downloaded from the Wii console. Demographic, spirometry, and sleep data were extracted from the Electronic Medical Records. The 6-minute walk distance (6-MWD) was measured before and after the 12-week exercise program. Pre-post outcomes were tested by Wilcoxon Signed-Rank Test. Results: Pre-post data were available in 6 of 9 patients; the remaining 3 reported they could not exercise because of balance problems. Among those participating, the duration (minutes/day, mean ± SD) and the caloric expenditure (calories/day, mean ± SD) of exercise were 40 ± 14, and 238 ± 134, respectively. The 6-MWD improved in OS patients who used Wii Fit (mean change = 30 ± 18 (SE) m, p=0.08). This change compared favorably with the OS patients who did not exercise (post-pre change = - 5 ± 39 m. There were no adverse events reported. Conclusion: A home-based exercise program using Wii Fit is feasible in improving functional capacity in patients with OS. Support (If Any): Office of Rural Health N06-FY15Q3-S1-P01507.